Comparative analysis of parental influence on adult golfers` psychological factors - Yang, J. H.; Yang, H. J.; Jung, S. C.; Bum, C.-H. (Research Quarterly for Exercise and Sport, 2025)
Background/Purpose: Athletes` psychological and physical factors or performance are influenced by external factors such as parents and others. Additionally, it is costly to practice golf and participate in a championship as it requires more parental accompaniment than other sports because it has characteristics that require training in outdoor driving range. Thus, the study compared overtraining, self-determined motivation, perceived performance, and the intention of sports dropout among adult golfers according to the type of parental accompaniment based on the relationship between Korean athletes and their parents. Parental accompaniment is crucial for immature young athletes for care and security, and it remains important for adult athletes to support their performance and success.